From the representative to the radical: how novel forms of participation can reform democracy and reduce existential risk. Issue 1 (1st January 2023) - Herbert, James
ABSTRACT: Existential risk is higher than is commonly thought. This risk can be reduced by improving our democratic processes and institutions. Local government has the opportunity, and therefore the responsibility, to experiment in this field. To inform this experimentation, this paper will discuss two novel types of participation. First, representative deliberative processes that reintroduce the Ancient Athenian practice of random selection, updating it wth modern statistical methods to ensure representativeness. Second, the 'radical' processes advocated for by RadicalxChange that permit mass participation but use a quadratic formula to accurately determine the strength of preferences, and not just their direction.